Bioconversion of sweet sorghum to ethanol - Najiah Nadir (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Ethanol or ethyl alcohol is one of the largest-volume chemicals utilized in both industrial and consumer products. It is not only an essential product for the alcoholic beverage industry, but it is also the most significantly used liquid biofuel either as a fuel or as a gasoline enhancer. Ethanol produced from agricultural crops continues to be of interest because of the renewable nature of the crops. Sweet sorghum (Sorghum bicolor (L.) Moench) is a type of starchy crops that has been considered as an important energy plant for the ethanol production. Both ethanol producers and researchers have shown that sweet sorghum is a suitable raw material for ethanol production because it is technically acceptable, fits the infrastructure, and can be economically viable, and could make a large contribution to the nation's fuel ethanol requirements. Conventional process for ethanol production from starch involved a three-stage process; liquefaction of starch by α-amylase, saccharification of liquefied starch by glucoamylase and followed by fermentation of sugar to ethanol using microorganisms. This research consisted of two main stages, which are two-step enzymatic hydrolysis and fermentation. Sweet sorghum grain was hydrolyzed by commercial α-amylase and glucoamylase enzymes, and then fermented by Saccharomyces cerevisiae yeast to produce ethanol. For hydrolysis process, the saccharification temperature gave the most significant influence on dextrose equivalent value, followed by glucoamylase dosage, liquefaction temperature, substrate concentration, saccharification time, liquefaction time, and lastly α-amylase dosage. The maximum glucose yield of 68.96% (g/g) was observed at 90°C of liquefaction temperature, 47°C of saccharification temperature, and 313 U/g of glucoamylase enzyme concentration. During fermentation, the initial pH of the media gave the most major effect on ethanol production, followed by amount of inoculum, agitation speed, amount of urea, fermentation temperature, and lastly amount of NPK (nitrogen, phosphorus, and potassium). The optimum fermentation conditions were obtained at 0.48% (w/w) of inoculum concentration, 6.5 of initial pH, and 60 rpm of agitation for maximum ethanol production of 71.45 g/L. The main limitation of this research was the saccharification and fermentation cannot be performed simultaneously. Normally, simultaneous saccharification and fermentation was carried out at a lower temperature (fermentation temperature instead of saccharification temperature) by using coculture method. However, since saccharification was done using commercial enzyme, the temperature higher than fermentation temperature is needed for saccharification. This higher temperature can deactivate the yeast thus reducing ethanol yield.